1996
DOI: 10.1056/nejm199608223350817
|View full text |Cite
|
Sign up to set email alerts
|

Prozac or Prilosec for Gastric Ulcer?

Abstract: We cannot acknowledge receipt of your letter, but we will notify you when we have made a decision about publication. We are unable to provide prepublication proofs. Please enclose a stamped, self-addressed envelope if you want unpublished material returned to you. Financial associations or other possible conflicts of interest must be disclosed. Submission of a letter constitutes permission for the Massachusetts Medical Society, its licensees, and its assignees to use it in the Journal 's various editions (prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The review of invented names for ethical drugs in Europe began in 1999 when EMA set up the Invented Name Review Group (NRG). This happened in response to papers in medical journals (Costable Jr and McKinley, 1996;Raffalli et al, 1997) which reported medication errors resulting from confusion caused by similar names given to ethical drugs, e.g. Losec 10 and Lasix 11 .…”
Section: An Inadvertent Policy Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review of invented names for ethical drugs in Europe began in 1999 when EMA set up the Invented Name Review Group (NRG). This happened in response to papers in medical journals (Costable Jr and McKinley, 1996;Raffalli et al, 1997) which reported medication errors resulting from confusion caused by similar names given to ethical drugs, e.g. Losec 10 and Lasix 11 .…”
Section: An Inadvertent Policy Experimentsmentioning
confidence: 99%
“…1 The aim is to protect consumers from medication errors that result from drug name confusion. Medical journals have repeatedly reported instances of confusion deriving from similar brand names for ethical drugs (Costable Jr and McKinley, 1996;Raffalli et al, 1997). Instances of lethal medication errors due to the confusion of drug names are documented.…”
Section: Introductionmentioning
confidence: 99%
“…Good communication is of importance when dealing with similar sounding medicine names. [3][4][5][6][7][8][9][10] Health professionals and patients tend to confuse drugs with similar names, thereby threatening patient safety. One out of four medication errors voluntarily reported in the US involves this type of drug-name confusion.…”
Section: Introductionmentioning
confidence: 99%
“…There are several examples of errors arising from similar sounding medicine names. 4,[7][8][9][10] In one, a hospitalised patient reported taking Paxil (paroxetine) at home, but was actually taking Plavix (clopidogrel). 8 The admitting physician misinterpreted the patient's pronunciation as Paxil and prescribed it.…”
Section: Introductionmentioning
confidence: 99%